Pajak Lingkungan untuk Pengendalian Pencemaran Udara Sektor Transportasi di Kota Yogyakarta - Astuti, Ninik Puji; Maryono, Maryono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Transportation grows rapidly along with high population growth. This sector has become an essential requirement for mobility and strongly supports the economy. In the period 2012-2016 the number of residents in Yogyakarta City increased by 23,732. This is accompanied by an increase of motor vehicles as much as 90,798 units. The number of motor vehicles correlates to fuel consumption. In 2012, fuel consumption in this city was recorded 107,089,000 liters and became 115,337,000 liters in 2017. Emissions resulting from fuel combustion by motor vehicles have an impact on the environment. The transport sector is known to contribute 70% of air pollution. Air pollution affects public health because it can trigger and/or aggravate some diseases, i.e. acute respiratory infections, cough, bronchitis, pneumonia, and eye irritation. This paper was written to determine the condition of air quality in Yogyakarta City as well as the opportunity of air pollution control using environmental tax. It is described descriptively based on data, literature, legal regulations, and prior research. Several ways have been done to control air pollution from mobile sources, but have not done from the economic side. Therefore it is necessary to develop environmental economic instruments. One of them is the study of environmental tax. This kind of study is expected to be an input for air pollution control.